Anti-CD47 Antibody As a Targeted Therapeutic Agent for Human Lung Cancer and Cancer Stem Cells - Liu, Liang; Zhang, Lin; Yang, Lin; Li, Hui; Li, Runmei; Yu, Jinpu; Yang, Lili; Wei, Feng; Yan, Cihui; Sun, Qian; Zhao, Hua; Yang, Fan; et al. (Frontiers in Immunology, 2017)
Accumulating evidence indicates that a small subset of cancer cells, termed the tumor-initiating cells (TICs) or cancer stem cells (CSCs), constitute a reservoir of self-sustaining cancer cells with the exclusive ability to self-renew and maintain the tumor mass. The CSCs play an important role in the tumor initiation, development, metastasis, relapse, and the ineffectiveness of conventional cancer therapies. CD47 is a ligand for SIRPα expressed on phagocytic cells, and functions to inhibit phagocytosis. Here we selected CD133 as the marker for lung CSCs according to previous reports. We analyzed lung cancer and matched adjacent normal (non-tumor) tissue and revealed that CD47 is overexpressed on lung cancer cells, especially on lung CSCs. The mRNA expression levels of CD47 and CD133 correlated with a decreased probability of survival for multiple types of lung cancer. Blocking CD47 function with anti-CD47 antibodies enabled macrophage phagocytosis of lung cancer cells and lung CSCs. Administration of anti-CD47 antibodies inhibited tumor growth in immunodeficient mouse xenotransplantation models established with lung cancer cells or lung CSCs and improved survival in tumor-bearing animals. These data indicate that CD47 is a valid target for cancer therapies, especially for anti-CSC therapies.